Pengaruh Saluran Distribusi, Gaya Hidup dan Kelompok Acuan Terhadap Minat Beli Ulang Air Minum Dalam Kemasan Merek Cleo di Surabaya - Munir, Misbachul; Putri, Amartya Fazrani Widya (Forum Kerjasama Pendidikan Tinggi, 2022)
Water is a basic element of living things, they cannot survive without water. If we consume less water, it can cause changes in plasma volume thermoregulation, hallucinations, and can even cause death. Meeting the human need for water creates bottled drinking water. With the existing brand competition, companies want to know the aspects that determine buying interest in money. The purpose of this study was to determine the role of distribution channels, lifestyle, and reference groups in the formation of repurchase interest in bottled water with the Cleo brand. This research is a quantitative research. The population of this study is an infinite number of consumers of Cleo brand bottled drinking water in Surabaya. The sample used was 100 respondents with multiple linear regression analysis techniques. The results of the three independent variables are proven to have a role to influence consumers when they take action to buy water in the Cleo brand packaging. Distribution channels, lifestyle, and reference groups have a real role in generating repurchase interest